High Level of Feeding in Addition to Dam Milk does not Improve Pre-weaning Growth Performance and Kleiber Ratio of Boer × Central Highland Kids - Tesema, Zeleke; Tilahun, Mekonnen; Zegeye, Asres; Lakew, Mesfin; Yizengaw, Liuel; Tiruneh, Solomon; Worku, Getachew; Kiros, Shanbel (Indian Journal of Animal Nutrition, 2019)
An experiment was conducted to evaluate pre-weaning growth performance and kleiber ratio of Boer crossbred goats under different levels of supplementation on dam milk. A 2 x 2 x 3 factorial ( 2 levels of sex, 2 levels of birth type and 3 levels of feed) in randomized complet block design was used to randomly allocate 36 one month age kids with an average initial body weight of 7.33±0.19 kg to feeding groups. The feeding groups were: Dam milk + grazing/browsing only (T1), dam milk + grazing /browsing + 1.26% of body weight concentrate mix (T2), dam milk + grazing/browsing + 2.1% of their body weight concentrate mix (T3). The average milk yield of does was 282, 332 and 394 g/day for T1, T2, and T3, respectively. Weaning weight of kids had a positive relationship (r=0.68) with milk yield of their dams. The pre-weaning average daily gain of kids was 85±9.01 g/day, 120.45±9.19 and 113.06±9.0 g/dayfor T1, T2, and T3, respectively. Sex had not a considerable influence on pre-weaning growth performance and kleiber ratio of kids. However, Single born kids exhibited higher weaning weight and average daily gain (119.52 g/day Vs 92.82 g/day) than twin born kids. Kids kept in T2 were 41.70% fast in growth than T1 and kids in T3 were 33.01% fast in growth than kids in T1. However, the difference between medium (T2) and high level of feeding (T3) was found to be non-significant (p>0.05). In conclusion, moderate level of feeding beside to their dam milk could improve weaning weight and pre-weaning growth rate of kids. Therefore, feeding high level of concentrate mix for kids during pre-weaning period is worthless.